PENGARUH LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA SISWA SMA AISYIYAH I PALEMBANG - Nina Fitriana; Lusia Nargis; Agus Priyatno (JURNAL KOMPETITIF, 2021)
This research is aimed at knowing the influence of the family environment on the entrepreneurship interests of high school students Aisyiyah I Palembang. The number of respondents in this study was 58 students.The results showed a correlation coefficient value of 0.683 meaning a strong and positive relationship between the family environment and entrepreneurship interests. The coefficient of determination of 0.466 means that 46.6% of werwirausah interest is influenced by the work environment and the remaining 53.4% is influenced by other variables not studied in the study.The regression equation obtained Y = 15.927 + 1,147 X which means the constant of 15,927 states that if there is no value of the family environment then the value of entrepreneurship interest is 15,927. The regression koofisien X of 1,147 states that every addition of one unit of family environmental value, the value of entrepreneurship interest increases by 1,147 units.Test t with significance value of 0.000 < 0.05. So it can be concluded that there is a significant influence of the family environment on entrepreneurship interests.